The Best Economic System for Saving: A Global Perspective - Mohamed, S.H Sheik; M, Nirmala; Arrohman, Baidawi; Fata, Zainol (International Conference on Islamic Economic (ICIE), 2025)
This study addresses the problem of uneven and often inadequate saving behavior across countries, which is closely related to differences in economic systems. The central issue examined is how capitalist, socialist, and mixed economic systems shape individual and national saving patterns amid global challenges such as rising living costs, consumerism, and economic uncertainty. The objective of this study is to analyze the relationship between economic system characteristics and saving behavior, while identifying the institutional, policy-related, and cultural factors that influence saving outcomes. The research employs a qualitative approach based on a literature review and comparative analysis of economic theories and global case studies. Data are analyzed descriptively and analytically to highlight the mechanisms through which different economic systems encourage or constrain saving behavior. The findings indicate that capitalist systems promote individual savings through market incentives and financial innovation, but they are often accompanied by inequality and overconsumption. Socialist systems emphasize state-managed savings and collective welfare, which can reduce individual motivation to save. Mixed economies demonstrate a more balanced approach by combining private initiative with social protection, thereby enhancing financial inclusion and economic resilience. This study contributes to the literature by emphasizing that an effective and sustainable saving system requires the integration of individual responsibility, strong institutional support, and supportive cultural values to ensure long-term economic growth and financial stability in an increasingly interconnected global economy.